Culture as sense determinant of understanding - Victor Fityo (Cхід)
The influence of culture within which interpreter exists onto understanding of the reality is analyzed. Cultural tradition is the sense background of local act of understanding. Interpreter as the bearer of the values of certain tradition understands according to the ways of interpreting the world within the given cultural tradition, his or her native linguistic picture of the world.